2023
DOI: 10.3389/fcvm.2023.1223244
|View full text |Cite
|
Sign up to set email alerts
|

A novel αB-crystallin R123W variant drives hypertrophic cardiomyopathy by promoting maladaptive calcium-dependent signal transduction

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiovascular disorder affecting 1 in 500 people in the general population. Characterized by asymmetric left ventricular hypertrophy, cardiomyocyte disarray and cardiac fibrosis, HCM is a highly complex disease with heterogenous clinical presentation, onset and complication. While mutations in sarcomere genes can account for a substantial proportion of familial cases of HCM, 40%–50% of HCM patients do not carry such sarcomere variants and the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 67 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…A recently identified mutation in CRYAB by Maron et al, the CRYAB R123W mutation, was discovered through genetic analysis in twins that developed hypertrophic cardiomyopathy with temporal concordance [ 35 , 36 ]. Follow-up mouse studies revealed that, unlike the previous two mutations, CRYAB R123W does not cause desmin aggregation but rather leads to cardiac dysfunction through sarcomere-independent mechanisms [ 36 ].…”
Section: Alpha-crystallin B Chain (Cryab)mentioning
confidence: 99%
See 4 more Smart Citations
“…A recently identified mutation in CRYAB by Maron et al, the CRYAB R123W mutation, was discovered through genetic analysis in twins that developed hypertrophic cardiomyopathy with temporal concordance [ 35 , 36 ]. Follow-up mouse studies revealed that, unlike the previous two mutations, CRYAB R123W does not cause desmin aggregation but rather leads to cardiac dysfunction through sarcomere-independent mechanisms [ 36 ].…”
Section: Alpha-crystallin B Chain (Cryab)mentioning
confidence: 99%
“…A recently identified mutation in CRYAB by Maron et al, the CRYAB R123W mutation, was discovered through genetic analysis in twins that developed hypertrophic cardiomyopathy with temporal concordance [ 35 , 36 ]. Follow-up mouse studies revealed that, unlike the previous two mutations, CRYAB R123W does not cause desmin aggregation but rather leads to cardiac dysfunction through sarcomere-independent mechanisms [ 36 ]. Knock-in mice with the CRYAB R123W mutation do not develop hypertrophic cardiomyopathy spontaneously but undergo a distinct remodeling process upon pressure overload via transverse aortic constriction [ 36 ].…”
Section: Alpha-crystallin B Chain (Cryab)mentioning
confidence: 99%
See 3 more Smart Citations